Bersama Menentukan Kehamilan Dalam Pernikahan - Khusnul Khotimah, Umi (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2021)
The concept of partnership and equality in marriage as mentioned in the Qur'an with the term